Arterial hypertension and associated factors in patients submitted to myocardial revascularization - Flávia Cortez Colósimo; Alexandre Gonçalves de Sousa; Gilmara Silveira da Silva; Raquel Ferrari Piotto; Angela Maria Geraldo Pierin (SciELO, 2015)
OBJECTIVE To identify the prevalence of arterial hypertension and associated factors in patients submitted to myocardial revascularization. METHOD Cross-sectional study using the database of a hospital in São Paulo (SP, Brazil) containing 3010 patients with coronary artery disease submitted to myocardial revascularization. A multiple logistic regression was performed to identify variables independently associated with hypertension (statistical significance: p<0.05). RESULTS Prevalence of hypertension was 82.8%. After the variables were adjusted, the associated factors were as follows: age, odds ratio (OR): OR=1.01; 95% confidence interval (CI): CI:1.00-1.02; female gender: (OR=1.77;CI:1.39-2.25); brown-skin race: (OR=1.53;CI:1.07-2.19); obesity: (OR=1.53;CI:1.13-2.06); diabetes: (OR=1.90;CI:1.52-2.39); dyslipidemia: (OR=1.51;CI:1.23-1.85); and creatinine>1.3: (OR=1.37;CI:1.09-1.72). CONCLUSION A high prevalence of arterial hypertension and association with both non-modifiable and modifiable factors was observed.